Cylindrically bent Laue analyzer in an X-ray Raman/emission spectrometer: performance tests and a comparison with spherically bent Bragg analyzers - Nozomu Hiraoka (Journal of Synchrotron Radiation, 2025)
The performances of a spherically bent Bragg analyzer and a cylindrically bent Laue analyzer in an X-ray Raman/emission spectrometer are compared. The reflectivity and energy resolution are evaluated from the intensity of the elastic scattering and the width of the energy distribution on a SiO2 glass sample. Widely used, Bragg analyzers display excellent performance at the photon energy E ≤ 10 keV. However, at higher E, the reflectivity and the resolution gradually deteriorate as E increases, showing poor performance above 20 keV. On the other hand, the reflectivity of the Laue analyzer gradually increases at E > 10 keV, displaying excellent reflectivity and good resolution around 20 keV. The Laue analyzer is suitable for X-ray absorption spectroscopy in high-energy-resolution fluorescence-detection mode or X-ray emission spectroscopy on 4d transition metal compounds. Furthermore, the X-ray Raman features of the lithium K-edge in LiF and the oxygen K-edge feature in H2O, measured by nine Bragg analyzers (2 m radius) at E ≃ 9.9 keV and by five Laue analyzers (1.4 m radius) at E ≃ 19.5 keV, have been compared. Similar count rates and resolutions are observed.